The Complex Interplay between Political Rule and Social Inequality: A Comparative Analysis - Younas, Ayesha; Fareed, Muhammad; Ali, Anwar (Annals of Human and Social Sciences, 2024)
This research paper aims to examine the relationship between political rule and social inequality in different governance systems. The background of the study is that it compares democracies (USA) with authoritarian regimes (North Korea, Saudi Arabia, UAE, Russia, and Iran). The methodology uses the Gini coefficient and poverty rates to measure social inequality and analyzes how economic regimes, political ideologies, and demographic factors contribute to disparities within societies. The results suggest that inflexible constitutions perpetuate social inequality, and individuals’ political culture and ideologies can either mitigate or worsen inequality. Centralized institutional frameworks with limited accountability and corruption are ineffective in addressing social inequality. While liberal democracies generally have lower Gini coefficients and poverty rates, this relationship is not always linear but multifaceted due to demographic, leadership and social variables among others. It is recommended that all regimes are equally responsible in providing services to their populations that prioritize social justice.